Enhancing Students' Collaboration Skills Through Scientific Approach-Based Worksheets in Human Sensory System Learning - Winda Juliana Siregar; Miza Nina Adlini (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Collaborative skills are one of the essential 21st-century competencies that students must possess and develop to face the challenges of modern learning. To support the achievement of this skill, innovative and contextual teaching materials are needed to enable students to learn actively through teamwork. This study aims to develop a Student Worksheet based on the Scientific Approach for the sensory system topic that is valid, practical, and effective. Methodology: Data collection was conducted using various instruments aligned with the 4D development model (Define, Design, Develop, Disseminate). In the Define stage was conducted through interviews and questionnaires for teachers and students to identify learning challenges. In the Design stage, the initial draft of the Student Worksheet was created based on the needs analysis, learning objectives, the syntax of the scientific approach, and collaboration skill indicators. During the Development stage, the worksheet underwent validation by content and media experts, and its practicality was tested through teacher and student questionnaires. Effectiveness was assessed using pretest and posttest instruments aligned with the indicators of the sensory system topic. In the dissemination stage, the revised worksheet was shared with biology teachers and underwent limited field testing. Findings: The analysis results show that the Student Worksheet is highly valid, with validation scores of 93.33 % for teaching media and 92.72 % for content. Practicality was rated high, with teacher and student scores of 91.38 % and 91.77 %, respectively. Effectiveness was indicated by an N-Gain score of 0.84 (high category). The scientific contribution of this research lies in the integration of the scientific approach into a collaborative Student Worksheet. Contribution: the novelty is reflected in the design of scientific activities based on teamwork. The theoretical implication supports the constructivist approach, while the practical implication offers a model of contextual science teaching media relevant to 21st-century learning